The Oxford History of British and Irish Catholicism: Vol. 2: Uncertainty and Change, 1641-1745. Edited by John Morrill & Liam Temple. Oxford: Oxford University Press, 2023. xxv + 324 pp. $ 165.00 cloth - Houliston, Victor (Church history, 2024)
The Oxford History of British and Irish Catholicism: Vol. 2: Uncertainty and Change, 1641-1745. Edited by John Morrill & Liam Temple. Oxford: Oxford University Press, 2023. xxv + 324 pp. $ 165.00 cloth. - Volume 93 Issue 3.